Single nucleotide polymorphisms in the Dicer gene modify the risk of systemic lupus erythematosus - Zhang, Jingjing; Zhao, Yufei; Wang, Song; Zhang, Shasha; Zhang, Xiaoyun; Peng, Chenxing; Liu, Qingyi (European journal of inflammation, 2024)
Objective MicroRNA-related single-nucleotide polymorphisms (miR-SNPs) can alter microRNA (miRNA) expression profiles, thereby influencing the risk of rheumatic diseases. Herrin a case control study, six miR-SNPs in miRNA processing machinery genes, namely RAN (rs14035), XPO5 (rs11077), Dicer (rs3742330), GEMIN3 (rs197412), GEMIN4 (rs2740348), and TNRC6B (rs9623117), were genotyped to assess their correlation with the risk of systemic lupus erythematosus (SLE). Methods We included 119 patients with SLE and 130 healthy controls. The genotypes of the six miR-SNPs were determined using polymerase chain reaction (PCR). Serum cytokine levels were assessed using a cytometric bead array, and fluorescent probe technology was used to determine plasma reactive oxygen species (ROS) levels. Results The AA genotype of Dicer was correlated with a 0.566-fold decreased risk of SLE compared with that of the AG + GG genotype (odds ratio, 0.566; 95% CI, 0.342–0.935; p = .026), and the rs3742330 A allele was associated with a significantly decreased risk of SLE (p = .035) compared with that of the rs3742330G allele. Additionally, AA genotype carriers exhibited lower levels of interleukin-6 (IL-6) in the blood (p = .013). Subsequent analysis revealed increased ROS production in patients with SLE than that in the controls (621.042 ± 425.285 vs 499.966 ± 302.273, p = .011). Conclusion Our findings suggest that ROS generation participates in SLE pathogenesis. The identification of Dicer gene SNP rs3742330 as a potential modifier of SLE risk via mediating IL-6 overproduction suggests a potential avenue for targeted interventions to manage SLE and its associated immune dysregulation.